Ameloblastic fibro-odontoma of the maxilla: Review of literature and report of a case - Barakha Nayak; Sangeeta Patankar; Komal Khot; B V Shobha; GopaI Sharma (Wolters Kluwer Medknow Publications, 2011)
Ameloblastic fibro-odontoma (AFO) is a rare benign mixed odontogenic tumor. It is a slow-growing generally asymptomatic lesion and more prevalent in children and adolescents. This article presents interesting case of ameloblastic fibro-odontoma involving anterior maxilla of 15-year-old male patient. Occlusal radiograph showed a large, well-demarcated radiolucency with radiopaque areas and miniature teeth like structures, radiographical presentation of this case was suggestive of compound odontoma. Histopathologically, the lesion was diagnosed as ameloblastic fibroodontoma.This article discusses about clinical, radiographical, histopathological aspect of ameloblastic fibroodontoma with review of literature